Developing A Model To Describe The Relationship Between The Factors Influencing Teachers’ Technostress While Teaching Online During A Crisis - Zuheir N G, Khlaif (2023)
This study explores the factors influencing technostress experienced by teachers while using new technology in online teaching during the crisis in a mandatory teaching environment based on their lived experience through using Microsoft Teams (MS Teams). Moreover, this study tried to discover the relationships between these factors, how they influence technostress and the type of relationships with continuance intention to use MS Teams.